p(1)=a+b+c=k^2, p(2)=4a+2b+c=l^2, p(3)=9a+3b+c=m^2, p(4)=16a+4b+c=n^2, p(5)=25a+5b+c διάφορο v^2. Το σύστημα των 3 πρώτων δίνει a=(m^2+k^2)/2-l^2, b=4l^2-(3m^2+5k^2)/2, c=3k^2+m^2-3l^2 και με αντικατάσταση στην 4η 3m^2+k^2-3l^2=n^2. Eπιλέγω k=5, l=3, m=3 και προκύπτει a=8, b=-40, c=57 δηλαδή το τριώνυμο p(x)=8x^2-40x+57. Eπίσης 3*9+25-3*9=25 τέλειο τετράγωνο, p(1)=25, p(2)=9, p(4)=9, p(4)=25, p(5)=57.
p(1)=a+b+c=k^2, p(2)=4a+2b+c=l^2, p(3)=9a+3b+c=m^2, p(4)=16a+4b+c=n^2, p(5)=25a+5b+c διάφορο v^2.
ΑπάντησηΔιαγραφήΤο σύστημα των 3 πρώτων δίνει a=(m^2+k^2)/2-l^2, b=4l^2-(3m^2+5k^2)/2, c=3k^2+m^2-3l^2 και με αντικατάσταση στην 4η
3m^2+k^2-3l^2=n^2.
Eπιλέγω k=5, l=3, m=3 και προκύπτει a=8, b=-40, c=57 δηλαδή το τριώνυμο p(x)=8x^2-40x+57.
Eπίσης 3*9+25-3*9=25 τέλειο τετράγωνο, p(1)=25, p(2)=9, p(4)=9, p(4)=25, p(5)=57.
Άψογος!!!!
ΑπάντησηΔιαγραφή